IMPLEMENTATION OF COOPERATIVE LEARNING TYPE TWO STAY TWO STRAY (TSTS) ON REACTION RATE MATTER TO TRAIN STUDENT’S SELF EFFICACY GRADE XI - RIZKIHATI PRASTIKA, FRISSA; NOVITA, DIAN (UNESA Journal of Chemical Education, 2018)
The aims of this research are to know implementation of cooperative learning model type Two Stay TwoStray on reaction rate matter, to describe student’s self efficacy and to know student’s reponses on reaction rate matter through the implementation of cooperative learning model type Two Stay Two Stray (TSTS). This research data analyzed by One Group Pretest-Posttest Design. This research was done for three meetings. Instruments that used in this research are implementation observation sheet, questionnaire and observation sheet of student’s self efficacy and student’s responses. It can be concluded that (1) Implementation of cooperative learning type Two Stay Two Stray was 100%; 93.75% and 97.92% in very good category, (2) Student’s self efficacy in level dimension is 76.65 in good category and strength dimension is 74.80 in good category, (3) Student’s responses is ≥61%, so it is in very good category. So it can be concluded that cooperative learning model type Two Stay Two Stray can be used to train student’s self efficacy at XI MIPA 3 SMA Negeri I Manyar.